Exploring the Relationship between Effective English Teaching and Students’ Performance in Secondary Schools in Bangladesh - Monira Jahan; Protiva Rani Karmaker (Yayasan Visi Intan Permata, 2026)
This study aimed to explore the relationship between effective English teaching and students’ performance in secondary schools in Bangladesh. The researchers used an exploratory research approach to conduct this study. Positivist and constructivist views were emphasized to produce quantitative and qualitative data for a more credible understanding of the investigated phenomena. The research was designed based upon a questionnaire survey and focus group discussion (FGD).90 teachers, purposively selected from twenty-four (24) randomly selected schools, constituted the sample of the study. Schools were located in Dhaka city and the rural areas of four different districts of the Dhaka division. Some robust findings were obtained from the study, and it is expected that these findings can provide guidelines for researchers, education experts, and policymakers to consider when making future policies.